1984
DOI: 10.1111/j.1365-3059.1984.tb00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Inoculating plant material by jet injection

Abstract: Both tubers and plants of potato were successfully inoculated with Erwinia carotovora subsp. itroseptica by means of a needle‐less medical jet injector. The instrument has also been used to infect potato tubers with Phorna exigua var. foveata, Fusarium solani var. coeruleum and F. sulphureum. It is suggested that high‐pressure injection is a potentially useful tool for introducing pathogens into plant materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…the discoloration of the stem tissue accompanying the bacterial rotting process, invariably originates from a rotting mother tuber (Pérombelon & Kelman, 1980) and therefore, the speed of the rotting process of the tuber tissue, as well as that of the stem tissue, could be regarded as putative components of resistance. Several methods have been described for the screening of tuber tissue resistance (see Allefs et al, 1995a) or stem tissue resistance (Hidalgo & Echandi, 1982;Hossain & Logan, 1983;Wastie, 1984;Lapwood & Read, 1986). In a previous study (Allefs et al, 1995b), it was shown that tuber tissue resistance of stored tubers of a set of 12 cultivars was not very well correlated with resistance to blackleg.…”
Section: Introductionmentioning
confidence: 99%
“…the discoloration of the stem tissue accompanying the bacterial rotting process, invariably originates from a rotting mother tuber (Pérombelon & Kelman, 1980) and therefore, the speed of the rotting process of the tuber tissue, as well as that of the stem tissue, could be regarded as putative components of resistance. Several methods have been described for the screening of tuber tissue resistance (see Allefs et al, 1995a) or stem tissue resistance (Hidalgo & Echandi, 1982;Hossain & Logan, 1983;Wastie, 1984;Lapwood & Read, 1986). In a previous study (Allefs et al, 1995b), it was shown that tuber tissue resistance of stored tubers of a set of 12 cultivars was not very well correlated with resistance to blackleg.…”
Section: Introductionmentioning
confidence: 99%
“…Potato genotypes have been screened for tuber resistance to erwinias in many countries and differences in resistance have been found (Dobias, 1973;Munzert & Hunnius, 1980;Bourne et al,, 1981;Hidalgo & Echandi, 1982;Ciampi-Panno & Andrade-Soto, 1984;Lapwood et al,, 1984). Different methods have been used to inoculate potato tubers with erwinias (De Boer & Kelman, 1978;Munzert & Hunnius, 1980;Bourne er a/., 1981;Lapwood era/., 1984;Wastie, 1984) but there are relatively few reports comparing results obtained with different methods (Dobias, 1973;Komorowska-Jedrys, 1975;Lapwood et ai, 1984). This paper reports investigations into the effects on cultivar resistance ranking of method of testing, choice of tuber tissue for inoculation, concentration of oxygen during tuber incubation, and method of assessing soft rot development.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for the inoculation of seed tubers prior to field assessment have been proposed. These include, dipping at harvest (Maas Geesteranus & Vruggink, 1976) or prior to planting (Logan & Copeland, 1979), stabbing with an impregnated tooth pick (Hossain & Logan, 1983) or needle (Logan, 1969;Lapwood & Legg, 1983), or injection by high pressure jet (Wastie, 1984), or under vacuum (Perombelon & Lowe, 1979;McGuire & Kelman, 1984).…”
Section: Introductionmentioning
confidence: 99%